Terlipressin-induced hyponatremic seizure in a child - Zaki, Syed Ahmed (Medknow Publications & Media Pvt Ltd, 2013)
Terlipressin, an analog of the natural hormone arginine-vasopressin, is a splanchnic constrictor that is used to control variceal bleeding in portal hypertension. It has a very good safety profile compared to vasopressin. Although rare, adverse effects such as hyponatremia and seizure can occur. We describe a 7-year-old male child who developed hyponatremia induced by infusion of terlipressin which resulted in a generalized seizure. After withdrawal of terlipressin, the serum sodium level became normal. Through this case, we emphasize the importance of monitoring patient's electrolyte levels during the course of terlipressin therapy.